Active labour market policies in economies based on tourism: The Balearic Islands experiences - Caparrós Alcaráz, Francisco (Cuadernos de Turismo, 2018)
Balearic Islands are a European-leading destination but the economic specialization in tourism activities produce dysfunctionalities in the labour market such as seasonality, a high demand of human resources in a short period, low level of educational attainment and underemployment. As counterpart, Active Labour Market Policies (ALMPs) are a set of interventions aimed to enhance human capital and to smooth career transitions. The aim of this paper is to shed light on these issues. Results suggest that Balearic Islands Employment Service (SOIB) is focused on counselling and training while other policies are not properly developed.